Computer vision based skin disease detection using machine learning - Jayeb, Ahmad Wasiq; Hore, Alvin Rahul; Anjum, Ramisa; Sadeque, Sohana Sanjana; Auqib, Syed Tahsin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.